ANALISIS KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS TANJUNG AGUNG KECAMATAN BATURAJA BARAT KABUPATEN OKU TAHUN 2022 - Yulis Marita; Ali Harokan; Arie Wahyudi (HEALTH CARE : JURNAL KESEHATAN, 2022)
Diarrhea is watery bowel movements usually at least three times in 24 hours, diarrhea most often occurs in children, especially those aged between 6 months and 2 years. Methods of this study aims to determine what factors were associated with the incidence of diarrhea in children under five in the working area of ​​Tanjung Agung Public Health Center, Baturaja Barat District, OKU Regency 2022. Quantitative method using a cross sectional research design. The population in this study was the visit of children under five at the Tanjung Agung Health Center, Baturaja Barat District, OKU Regency. The collecting sample method of this study was accidental sampling technique. The sample numbers of in this study were 74 respondents. Collecting data in this study using a questionnaire.The results of statistical test analysis using the chi-square test showed that there was a significant relationship (p < 0.05) for age (p value 0.000), knowledge (p value 0.014), nutritional status (p value 0.000), clean water sources (p value 0.000), ownership of latrines (p value 0.000) and hand washing habits (p value 0.000). From the results of multivariate analysis, it was found that the dominant factor for the incidence of diarrhea in children under five in the working area of ​​Tanjung Agung Public Health Center, Baturaja Barat District, OKU Regency 2022, namely age (p value 0.000) (OR 28.750) Conclusion: there was a significant relationship (p < 0.05) among age, knowledge, nutritional status, clean water sources, latrine ownership and hand washing habits. The dominant factor for the incidence of diarrhea in children under five in the working area of ​​Tanjung Agung Public Health Center, Baturaja Barat District, OKU Regency 2022, was age.